Ključi od labirinta: o slovenski poeziji - Jensterle-Doležal, Alenka (University of Maribor Press, 2017)
The Keys of the Labyrinth: on Slovene Poetry. In the following literary monograph we investigate the typical features of Slovene poetry: themes, motifs, shapes, ideas, images and their modification, lyrical subject, poetic strategies and changing forms from France Prešeren to postmodernism. We also focus on the reception and context of the Slovene poetry and research changing features in the development of poetry in the 19th a nd 20th century. In the focus of our research interest is the text and its intertextuality.